Theoretical and numerical investigation of a new 3-axis SU-8 MEMS piezoresistive accelerometer. (October 2022) - Khlifi, Awatef; Ahmed, Aftab; Mezghani, Brahim; Patkar, Rajul; Dixit, Pradeep; Tounsi, Fares; Baghini, Maryam Shojaei
Abstract: This paper investigates the static and dynamic performances of a new enhanced design of 3-axis MEMS polymer piezoresistive accelerometer. Its key geometric parameters are optimized using a developed numerical finite element model (FEM). Using FEM analysis, the evaluated induced stress fields show a clear improvement compared to two similar silicon-based designs found in literature. Under 100 g z-axis accelerations, the proposed design proof-mass deflection is 21.78 μm and the maximum induced stress in the beams is 13.2 MPa. With the incorporation of SU-8/Carbon Black (CB) piezoresistive layers in locations of maximum induced stress, the piezoresistive analysis is performed to deduce the variations in resistance values. Using FEM dynamic analysis, the Eigenfrequency is 1.08 kHz and the quality factor is 5.55. In addition, a complete analytical model is developed and we show that values from derived expressions are in good agreement with results obtained from FEM simulations. The details of a low-cost and simple fabrication process-flow is provided for the proposed design.